Radiative transfer corrections for accurate spectroscopic measurements of volcanic gas emissions - Kern, Christoph; Deutschmann, Tim; Vogel, Leif; Wöhrbach, Markus; Wagner, Thomas; Platt, Ulrich (Bulletin of volcanology, 2010)
There is widespread use of passive remote sensing techniques to quantify trace gas column densities in volcanic plumes utilizing scattered sunlight as a light source. Examples include passive DOAS, COSPEC, and the SO2 camera. In order to calculate trace gas concentrations or volcanic emission fluxes, knowledge about the optical path through the plume is necessary. In the past, a straight photon path through the plume has always been assumed although it was known that this is not always true. Here we present the results of model studies conducted specifically to quantify the effects of realistic radiative transfer in and around volcanic plumes on ground-based remote sensing measurements of SO2. The results show that measurements conducted without additional information on average photon paths can be inaccurate under certain conditions, with possible errors spanning more than an order of magnitude. Both over and underestimation of the true column density can occur. Actual errors depend on parameters such as distance between instrument and plume, plume SO2 concentration, plume aerosol load, as well as aerosol conditions in the ambient atmosphere. As an example, a measurement conducted with an SO2 camera is discussed, the results of which can only be correctly interpreted if realistic radiative transfer is considered. Finally, a method is presented which for the first time allows the retrieval of actual average photon paths in spectroscopic (i.e. DOAS) measurements of adequate resolution. By allowing for a wavelength dependent column density during the evaluation of DOAS measurements, we show how radiative transfer effects can be corrected using information inherently available in the measured spectra, thus greatly enhancing the accuracy of DOAS measurements of volcanic emissions.